Drift in Mesopotamian pottery: Samarra pottery as a model - Al-Obaidi, Mohammed Jassim (Al-Adab Journal, 2021)
Of the modern sciences that have worked in the arena of cultural, scientific, artistic and academic ideologies, which began to cover the arena around us with its characters, connotations, symbols and intersecting techniques at the beginning of the twentieth century, the "displacement theory", which carried in its engines the cultural references that began to pass through important stages in most contemporary arts, including plastic arts in general and ceramic arts in particular. Despite the existence of many alternatives, this "shift" theory began to control the internal structures of the pottery works, in a direction that specifically highlights the pottery and ceramic work, Especially the ancient Mesopotamian pottery works, this accumulated product and witness to the action of all the exciting achievements, which have become effective since ancient times until they are summoned to contemporary and in turn contribute to directing the steps in the right path, and it becomes one of the concerns of contemporary thought. Which began in a system of prevailing systems in an artistic and experimental language to take a picture of integration in this field that establishes the foundations of that theory, which reached a great significance in the early twentieth century, and these steps are still vigorous and important with artistic productions that increase significantly to meet the requirements of art, Artistic production began to increase steadily - the fullest share of contemporary art was dedicated to satisfying the prevailing public taste and did not possess long-lasting properties.